Ordbildningsmönster och ordrepresentation i svenska ordböcker från 1500- och 1600-talen - Johansson, Monica (LexicoNordica, 2000)
No dictionary has collected or will ever be able to collect all words used in the sixteenth and seventeenth century. Yet there are four Swedish dictionaries which show parts of the vocabulary used in that time or words that may be created for example by translation. Three of these dictionaries are based on the European Latin dictionary tradition, while the fourth seems to be a vernacular product. The dictionaries with Latin as source language are often more or less copies of a Latin dictionary but with Swedish as target language. In three of the dictionaries from this time, compound words, derivations and phrases are very frequent as target words as well as source words. But in the fourth dictionary by Ericus Schroderus most of the Swedish words are stemwords, probably collected in Swedish language in use.